A natural language interface for a music database - Diz Pico, Jorge (My University, 2011)
We present an interface for a music database in which the user asks questions and the system replies with the exact information desired. Natural language parsing with the Grammatical Framework was used for input and output processing as to offer multilingual capabilities. The code architecture, from interface to database connection and results treatment, was built with Haskell. Arrows and an increased degree of function modularity were employed, looking for flexibility for future expansions.
Keywords: Datavetenskap (datalogi); Computer Science